Exploring the impact of AI-powered language tools on language learning attitudes and test anxiety among undergraduates - Zuraina, Ali; Amy Zulaikha, Mohd Ali; Mohd Amir Izuddin, Mohamad Ghazali; Nur Najmiyah, Jaafar; Rahmah, Mokhtar (IGI Global, 2025)
This study examined how undergraduate students' views on language learning and test anxiety were influenced by AI-Powered Language Tools (AiLTs). Data from 55 participants from a survey indicated that familiarity with AiLTs enhanced attitudes, despite concerns about the impersonal nature compared to traditional teaching. Significant positive correlations were found between test anxiety levels and AiLTs usage frequency and experience. Higher anxiety levels were associated with increased AiLTs usage. Notably, familiarity with AiLTs did not show a clear link to test anxiety. These results emphasize the importance of considering test anxiety when assessing AiLTs usage. Educators and policymakers can use this study to enhance language learning in higher education with AI technology while addressing testrelated concerns.